Verbal and nonverbal culture-fair challenges - Trigo, B. R. de O.; Ferreira, A. I.; Almeida, P. (Psychological Test Adaptation and Development, 2024)
Optimizing selection processes is a multilayer beneficial achievement. Moreover, task-switching is a commonly required ability in a variety of jobs (e.g., programmers). The present study aims to develop a rapid task-switching assessment for the Portuguese-speaking population that integrates verbal content with nonverbal components. One hundred and sixty-four participants answered the task-switching test, and 78 of those were evaluated in terms of their overall job performance in 2020, 2021, and 2022 by their managers. Fifteen items were kept in the final version of the tool, across three tasks. Statistical analyses showed there was positive evidence for the acceptable psychometric properties of the assessment tool and how the task-switching performance of the test correlated to job performance.